UPAYA GURU BIMBINGAN DAN KONSELING MEMPERBAIKI CARA BELAJAR SISWA MELALUI BIMBINGAN BELAJAR DENGAN METODE BIMBINGAN KLASIKAL PADA SISWA KELAS XI SMA NEGERI 1 SUNGAI PUAR - Naldo Naldo; Sri Hartati (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Student learning problems are very complex and varied, such as: lying, leaving without permission, stealing, cheating, low learning discipline, low learning motivation, low learning achievement, not necessarily achieved by lazy students but caused by wrong attitudes and ways of learning. Tutoring at school for class higher. Therefore, teaching and learning activities in class XI students at SMA 1 Sungai Puar must be activated into guidance and counseling. One method of implementing tutoring at high school level is through teaching and learning activities with a guidance nuance. The operationalization is the values of learning guidance services provided to students on the sidelines or even simultaneously with the guidance that will be provided by guidance and counseling teachers. Learning difficulties are a problem that often arises among students, this problem is caused by various factors, including internal factors and external factors. Learning difficulties are characterized by low learning outcomes, students are unable to learn well, and have difficulty understanding what they are learning. So that in the end it can cause student learning achievement to be at the lowest level. The type and level of difficulty experienced by students is not the same conceptually, intelligence and learning motivation for each student. Student learning difficulties are generally divided into two categories, namely learning difficulties related to development (attention, memory, movement and perception disorders, language and thinking) and academic learning difficulties such as learning mathematics and English.